2019
DOI: 10.1140/epje/i2019-11851-6
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary analysis of Diffusion Coefficient Measurements in ternary mIXtures 4 (DCMIX4) experiment on board the International Space Station

Abstract: In the frame of the Diffusion Coefficient Measurements in ternary mIXtures 4 (DCMIX4) project the thermodiffusion experiments were conducted on the International Space Station (ISS) in the Selectable Optical Diagnostics Instrument (SODI) which is on orbit since 2009. We describe the results of the preliminary analysis of images downloaded during the execution of DCMIX4 in order to check the quality of the running experiments and, if needed, adjust the experiment parameters for the following runs. The quick ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Thermodiffusion experiments in ternary mixtures are performed on ground, by using different optical techniques [10,14,17,18], or in microgravity in order to avoid both convection and sedimentation. The thermodynamic characterization of ternary mixtures is one of the objectives of the following ESA projects: Diffusion Coefficient Measurements in ternary mIXtures (DCMIX) [18][19][20][21][22][23], Soret Coefficients in Crude Oil (SCCO) [1,[24][25][26][27] and Giant Fluctuations [28], as further elaborated in a recent colloquium paper [29].…”
Section: Introductionmentioning
confidence: 99%
“…Thermodiffusion experiments in ternary mixtures are performed on ground, by using different optical techniques [10,14,17,18], or in microgravity in order to avoid both convection and sedimentation. The thermodynamic characterization of ternary mixtures is one of the objectives of the following ESA projects: Diffusion Coefficient Measurements in ternary mIXtures (DCMIX) [18][19][20][21][22][23], Soret Coefficients in Crude Oil (SCCO) [1,[24][25][26][27] and Giant Fluctuations [28], as further elaborated in a recent colloquium paper [29].…”
Section: Introductionmentioning
confidence: 99%
“…Under microgravity conditions the Soret effect can be used to generate a concentration gradient in a fluid mixture under controlled conditions by applying a temperature gradient to the layer of mixture, with the advantage that experiments can be iterated at will by imposing/removing the thermal gradient. This method has been exploited during several experiment s of t he European Space Agency on thermodiffusion under microgravity conditions (Braibanti et al 2019), which benefited from the fact that the absence of gravity allows to investigate purely thermodiffusive processes, in the absence of convective instabilities.…”
Section: Thermodiffusionmentioning
confidence: 99%
“…The results obtained with GRADFLEX allowed to establish that linearized hydrodynamics is suitable to provide a fully quantitative description of the static structure factor of non-equilibrium fluctuations under the ideal conditions where the amplitude of fluctuations is small, and the diffusive process is stationary. At the same time, the development of the DCMIX project of the European Space Agency showed the interest of a wide community of scientists in the investigation of mass transport processes in multi-component liquid mixtures (Bou-Ali et al 2015;Galand et al 2019;Shevtsova et al 2014;Triller et al 2018;Mialdun et al 2019). Multi component mixtures exhibit a rich stability diagram, where the stability of the sample in the presence of gravity is compromised by the presence of double diffusion processes, which can lead to convective instabilities even when the initial density profile of the sample is stable (Šeta et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…13,[17][18][19] The DCMIX3 system is composed of water, ethanol, and triethylene glycol, 20 and the last campaign, DCMIX4, includes three additional mixtures of the system toluene, methanol, and cyclohexane; one mixture containing fullerene and a polymer diluted in a binary solvent. 21 The processing of the ISS data revealed that the final results were sensitive to the applied methodology. This is especially interesting in systems close to the stability boundary.…”
Section: Introductionmentioning
confidence: 99%